Pengaruh Celebrity Endorser, Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Produk MS Glow (Pada Mahasiswa FEB Prodi Manajemen Universitas Islam Malang) - Silvia Ayu Wulandari; Siti Asiyah; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to describe celebrity endorsers, promotions, product quality, purchasing decisions and influence the influence of celebrity endorsers, promotions and product quality on purchasing decisions for MS Glow products. This study used an explanatory research method with a quantitative approach and the data collection method in this study was carried out by distributing online questionnaires using snowball sampling. The sample used in this research was 60 students from the Faculty of Business Economics, Islamic University of Malang, class of 2019 from the Management Study Program. Data analysis used validity test, reliability test, multicollinearity test, heteroscedasticity test, multiple linear analysis, F test (simultaneous), t test (partial), and coefficient of determination test (adjusted R2). The results of this study indicate that simultaneously the variables celebrity endorser, promotion and product quality have a positive effect, partially celebrity endorser has a positive and not significant effect, promotion has a positive and insignificant effect, while product quality has a positive and significant effect on purchasing decisions. on purchasing decisions This study uses a type of quantitative research. Keywords: Celebrity Endorser, Promotion, Product Quality, Purchasing Decisions